2022
DOI: 10.3389/fcvm.2022.868850
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Causal Associations of Atopic Dermatitis With Heart Failure and Other Cardiovascular Outcomes: A Mendelian Randomization Study

Abstract: Background and AimsObservational epidemiological studies have suggested that atopic dermatitis (AD) was associated with an increased risk of cardiovascular diseases (CVDs). However, causality remains to be established. In the present study, Mendelian randomization (MR) analyses were used to evaluate whether AD and CVDs are causally associated.MethodsThis study was based on summary statistics of genome-wide association studies (GWASs) for a set of cardiovascular outcomes including heart failure (HF), coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“… 53 No association between atopic dermatitis and cardiovascular events has also been reported. 54 , 55 The link between atopic dermatitis and diabetes mellitus is inconclusive. One study demonstrated that genetically predicted atopic dermatitis is a risk factor for type 2 diabetes, with an odds ratio of 1.07 (95% CI 1.02–1.11, p = 0.003), 56 while another study showed that the prevalence of atopic dermatitis is lower in individuals with type 2 diabetes than in those without type 2 diabetes.…”
Section: Association Of the Skin With Aging-associated Conditionsmentioning
confidence: 99%
“… 53 No association between atopic dermatitis and cardiovascular events has also been reported. 54 , 55 The link between atopic dermatitis and diabetes mellitus is inconclusive. One study demonstrated that genetically predicted atopic dermatitis is a risk factor for type 2 diabetes, with an odds ratio of 1.07 (95% CI 1.02–1.11, p = 0.003), 56 while another study showed that the prevalence of atopic dermatitis is lower in individuals with type 2 diabetes than in those without type 2 diabetes.…”
Section: Association Of the Skin With Aging-associated Conditionsmentioning
confidence: 99%